Integrating Space Science and Local Wisdom through Creative Learning: Indonesian Case Study - Wibowo, Antonia Rahayu Rosaria (International Journal of Multidisciplinary Sciences, 2025)
Indonesia has various local wisdom. The local wisdom has been inherited from generation to generation. It is also integrated into formal education. Integrating local wisdom and education is also practiced in isolated areas like Gunung Katun Tanjungan village in Tulang Bawang Udik subdistrict, Tulang Bawang Barat regency, Lampung province. This village only has one school and it is an elementary school. Without a strong communication signal, students in this village cannot access educative information. In this limitation, creative learning is needed so students can get their right to education. This article seeks to investigate the author's creative learning strategy for teaching science, namely the solar system to 6th graders to connect space science and local wisdom. This article was written based on the author’s experience. Then, the experience was analyzed using creative learning theory. The analysis was carried out by matching the variable mentioned in the creative learning theory and the author’s experience. The conclusion shows that creative learning can create a fun learning environment to overcome the limitations in an isolated area. Moreover, creative learning has helped students to relate space science and local wisdom so space science can be a part of their lives.